Nilai-Nilai Pendidikan dalam Sholat - M. Nur Kholis Al Amin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: Islam teaches to no dichotomy between the world of knowledge with knowledge of the afterlife. however, Islam is more likely to emphasize his people to gain the knowledge to keep both scientific study. this indicates that Islam educate his people to always learn, both in terms of vertical worship to the Creator or social structuring in social life. One of the institutionalization of worship that have educational value of learning in public life is â€œsholatâ€. In this paper the authors try to find educational value contained in the institutionalization of â€œsholatâ€, Which was known by some Muslims as a nuanced vertical worship alone. Keywords : value, education, sholat.